Iron Complexes with Antarctic Krill–Derived Peptides Show Superior Effectiveness to Their Original Protein–Iron Complexes in Mice with Iron Deficiency Anemia - Shengjie Hu; Songyi Lin; Qi Feng; Xueqing He; Haowei Xu; Lei Chen; Na Sun (Nutrients, 2023)
Antarctic krill protein–iron complex and peptide–iron complex were acquired to investigate their iron bioavailability, expression of iron-regulated genes, and in vivo antioxidant capacity. Results indicated that the Antarctic krill peptide–iron complex significantly increased the hemoglobin (Hb), serum iron (SI), and iron contents in the liver and spleen in iron-deficiency anemia (IDA) mice (p < 0.05) compared with those of the Antarctic krill protein–iron complex. Despite the gene expressions of the divalent metal transporter 1(DMT1), the transferrin (Tf), and the transferrin receptor (TfR) being better regulated by both Antarctic krill peptide–iron complex and protein–iron complex, the relative iron bioavailability of the Antarctic krill peptide–iron complex group (152.53 ± 21.05%) was significantly higher than that of the protein–iron complex group (112.75 ± 9.60%) (p < 0.05). Moreover, Antarctic krill peptide–iron complex could enhance the antioxidant enzyme activities of superoxidase dismutase (SOD) and glutathione peroxidase (GSH-Px), reduce the malondialdehyde (MDA) level in IDA mice compared with the protein–iron complex, and reduce the cell damage caused by IDA. Therefore, these results indicated that Antarctic krill peptide–iron complex could be used as a highly efficient and multifunctional iron supplement.